Outcome of surgery in different Parotid Neoplasms (Bangladesh Journal of Otorhinolaryngology, 2015)
Objective: To determine outcome of surgery in different parotid neoplasms. Study design: Cross sectional study from August 2010 to July 2014. Settings: Department of Otolaryngology and Head-Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Method: 60 postoperative patients of different parotid neoplasms were included in this study. 33 were males and 27 were females between 21 years to 80 years who were treated between August 2010 to July 2014. The study based on history, clinical examinations, radiological, laboratory, cytology reports and histopathological examination. Results: Majority of the patients were within 41 to 70 years of age. Frequency of benign tumour were more in 4th and 5th decade 42(87.5%) and malignant tumour in 5th and 6th decade 8(66.7%). Common presenting features were pain 8(66.7%), skin involvement 3(25.0%), facial nerve palsy 3(25.0%), metastatic neck nodes 3(25.0%) in malignant cases. In benign cases 45(93.7%) were pleomorphic adenoma, 3(6.25%) Warthins tumour. In malignant cases mucoepidermoid carcinoma were 7(58.3%), adenoid cystic carcinoma 3(25.0%). In benign parotid tumour, superficial parotidectomy were done in 45(93.75%) and total conservative parotidectomy 3(6.25%). In malignant tumour total conservative parotidectomy were done 5(41.7%), total radical parotidectomy done 4(33.3%), extended radical parotidectomy 3(25%). Histopathological study showed 45(93.75%) were in pleomorphic adenoma, 7(58.3%) mucoepidemoid carcinoma. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22023 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 80-86